2013
DOI: 10.1155/2013/267959
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Effect and Central Autonomic Regulation

Abstract: Acupuncture is a therapeutic technique and part of traditional Chinese medicine (TCM). Acupuncture has clinical efficacy on various autonomic nerve-related disorders, such as cardiovascular diseases, epilepsy, anxiety and nervousness, circadian rhythm disorders, polycystic ovary syndrome (PCOS) and subfertility. An increasing number of studies have demonstrated that acupuncture can control autonomic nerve system (ANS) functions including blood pressure, pupil size, skin conductance, skin temperature, muscle sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 76 publications
0
64
0
2
Order By: Relevance
“…Although using a targeted postnatal intervention, we have recently demonstrated reversibility of the perinatal nicotine-induced lung phenotype [18]; however, short of the cessation of smoking during pregnancy (http://www.cdc.gov/tobacco), which is not always achievable, a more practical strategy would be to safely and proactively block perinatal nicotine-induced lung damage before it occurs. Clinical and animal studies have demonstrated that acupuncture modulates a variety of the body’s patho-physiological responses, including hypothalamic-pituitary-adrenal (HPA) axis, immune function, energy metabolism, and microcirculation, potentially affecting the development of many organ systems including the respiratory tract [19–23]; however, whether acupuncture has a protective effect on the lung damage caused by perinatal nicotine exposure is not known. We hypothesized that by modulating key regulators of lung development, acupuncture blocks the development of the perinatal nicotine-induced lung phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Although using a targeted postnatal intervention, we have recently demonstrated reversibility of the perinatal nicotine-induced lung phenotype [18]; however, short of the cessation of smoking during pregnancy (http://www.cdc.gov/tobacco), which is not always achievable, a more practical strategy would be to safely and proactively block perinatal nicotine-induced lung damage before it occurs. Clinical and animal studies have demonstrated that acupuncture modulates a variety of the body’s patho-physiological responses, including hypothalamic-pituitary-adrenal (HPA) axis, immune function, energy metabolism, and microcirculation, potentially affecting the development of many organ systems including the respiratory tract [19–23]; however, whether acupuncture has a protective effect on the lung damage caused by perinatal nicotine exposure is not known. We hypothesized that by modulating key regulators of lung development, acupuncture blocks the development of the perinatal nicotine-induced lung phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Then opioids regulate also ANS: balancing it and leading to wellbeing condition, as Li Qian [11] studied in 2013…”
Section: Main Text and Discussionmentioning
confidence: 99%
“…Additionally, effects have been described related to touch and pressure to the skin [43][44][45][46], physiological effects of shallow insertion needling [47][48][49][50][51], non-inserted needling [44,52], deeper needling with varying forms of manipulation [14,42] including electrical stimulation of the needles [40,42,53,54]. Other studies demonstrate that acupuncture can also create effects due to modulation of the somato-sensory system [55], autonomic nervous system [51,[56][57][58], and microcirculatory [48,59], antiinflammatory [60,61] and immunological effects [62][63][64]. It is believed that moxibustion may also stimulate a wide spectrum of physiological changes including effects on the immune system and the blood [4].…”
Section: Mechanismsmentioning
confidence: 99%